The hydrochemistry of Tigris River in Baghdad city, Iraq - Abdulazeez, Haneen Zaid; Al-Shamma’a , Ayser Mohammed; Saud, Qays Jasim (Iraqi Journal of Science, 2020)
The primary objective of this study was to investigate the current status of water-quality conditions and assessment it in the Tigris River, Baghdad, Iraq, and to determine how those conditions are changing over time of pollution if any. A series of Hydrochemical tests were carried out to ascertain the influence of major Cations and Anions, Total Dissolved Solids (TDS), Electrical Conductivity (EC) and Potential of hydrogen (pH) on the quality of water. To assess the environmental pollution of the study area: 34 water samples were collected along Tigris River from north to south Baghdad City; 17 on January 2019 and 17 on April 2019. Result of the test were compared with the World Health Organization standards, and showed that all the ions in addition of EC and TDS are within their acceptable limits, except for samples number 7 and 16where Sulfate concertation was above the acceptable limits. Therefor the Tigris River water in most of the study area is acceptable for all kinds of consumption. The most common water type in the area was Ca Na Mg- SO4 Cl HCO3 in January 2019 and Na Ca Mg- SO4 Cl in April 2019.